The Formation and Dynamics of Colonial “Lived Spaces”: Urban Space and Society in Colonial Hanoi, 1883–1916 - Hoang, Nam Khanh (The Columbia Journal of Asia, 2025)
This study examines the nuanced experiences and perceptions of urban space among different social groups in colonial Hanoi in the late nineteenth and early twentieth centuries by analyzing the French colonial agendas, as reflected through modern urban planning and practices, and its reception among the colonial urban inhabitants, as suggested through their responses to the Statue of Liberty—a colonial urban monument. While existing scholarship has often framed colonial cities as stages for consolidating imperial power, introducing Western ideals of modernity, and forming systems of oppression and exploitation against colonial subjects, it has often overlooked the perceptions and experiences of colonial settlers and native communities, who account for the majority of the city’s population. To address this gap, this study utilizes Henri Lefebvre’s notion of “lived spaces” to explore the multiple layers of experiences of colonial subjects reflected in memoirs, records, and testimonies. A detailed analysis of these sources suggests that colonial subjects were not passive recipients of the colonial agendas but rather active agents constantly challenging and reinterpreting the imposed ideologies according to their interests. Hence, the colonial city, rather than a stage for advancing colonial rule, was a “contact zone” where colonial agendas clashed with subalterns’ resistance.